Laticifers in Sapindaceae - Montes, Maria Camila Medina (2017)
Laticifers are poorly known among Sapindaceae species. They have only been cited in few works, without a description of its structure, ontogeny and histochemistry, which is of great importance to classify and distinguish them from idioblasts that are cells usually observed in the same organs. Therefore, this work aimed to verify the presence of laticifers in 64 species belonging to 21 genera of Sapindaceae, and to analyze their anatomical aspects, latex composition and evolution within the family. The material obtained from herbaria was rehydrated and embedded in methacrylate, according to the usual techniques in plant anatomy. For histochemical analysis fresh or Paraplast-embedded shoots were used. The presence of articulated nonanastomosing laticifers was confirmed for 15 genera from two subfamilies, being described for the first time in some genera. Apparently, this secretory structure arose six times during evolution of the family. They originate early in the development of shoot apex when the tissues are still in meristematic phase and distributed generally in cortex, phloem and pith. The histochemical tests allowed the observation of lipids, carbohydrates, proteins, alkaloids, and phenolic compounds in the latex. Callose and suberin was also detected in laticifer walls of some species, helping in the interpretation of the infratribal relationships. In general laticifers in the family are small, short and narrow in comparison with other families, and for this reason, for a long time, remained unrecorded in the literature. Presence or absence of laticifers can be used as a character that can help in taxonomic resolution and establishment of relations among groups within Sapindaceae